Efficient and Reliable Dissemination in Mobile Ad Hoc Networks by Location Extrapolation - Adnan Agbaria; Muhamad Hugerat; Roy Friedman (Journal of Computer Networks and Communications)
Data dissemination is an important service in mobile ad hoc networks (MANETs). The main objective of this paper is to present a dissemination protocol, called locBcast, which utilizes positioning information to obtain efficient dissemination trees with low-control overhead. This paper includes an extensive simulation study that compares locBast with selfP, dominantP, fooding, and a couple of probabilistic-/counter-based protocols. It is shown that locBcast behaves similar to or better than those protocols and is especially useful in the following challenging environments: the message sizes are large, the network is dense, and nodes are highly mobile.